Laughing matters : Understanding film, television and radio comedy - Mundy, John; White, Glyn (Book collections on Project MUSE., 2018)
Laughing Matters is an undergraduate level textbook taking an analytic approach to film, television and radio comedy, providing an accessible overview of its forms and contexts. The introduction explains the value of studying comedy, concisely outlines the approach taken and summarises the relevant theories. The subsequent chapters are divided into two parts. The first part examines the specific forms comedy has taken as a constant and key element in film and broadcast comedy from their origins to the present. The second part shows how the genre gravitates towards contentious issues in British and American culture as it finds humour in the boundaries of class, gender, sexuality, race and logic. The authorst cover silent cinema comedy, early sound film comedy, Romantic film comedy, radio, television situation and sketch comedy, comedy and genre, animations, issues of gender and sexuality, taste, and race and ethnicity.